2004
DOI: 10.1111/j.1524-4725.2004.30000.x
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Technique of the Antiptosis Subdermal Suspension Thread

Abstract: Our case study strongly suggests that the Aptos subdermal suspension thread technique provides an effective and much safer alternative to current facioplasty procedures for facial rejuvenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 7 publications
1
47
0
Order By: Relevance
“…Previously used for years in cosmetic surgery with excellent results [12][13][14], this type of anchoring columns provides immediate fixation. The polypropylene monofilament mesh provides good results and low rates of healing defects.…”
Section: Discussionmentioning
confidence: 99%
“…Previously used for years in cosmetic surgery with excellent results [12][13][14], this type of anchoring columns provides immediate fixation. The polypropylene monofilament mesh provides good results and low rates of healing defects.…”
Section: Discussionmentioning
confidence: 99%
“…13 Their results were not as favorable overall as those in the study by Sulamandize et al, 10 as they rated as good to fair the results In all, 52 of the 350 patients required some type of revision but the authors stated that revision became less frequent with increased experience. At the 36-month follow-up visit, original results were maintained in 60% of the patients.…”
Section: Commentmentioning
confidence: 82%
“…Extrusion is unusual (1% of the cases). Another authors have found thread visibility, migration, and exposure; linear bleeding along the needle course; skin dimpling; hypocorrection and hypercorrection; transient paresthesias; and a small number of cases of injury to major vessels, nerve branches, and parotid capsule/duct [5] mild asymmetry, ecchymosis, erythema, bleeding, swelling, and discomfort were the only minor. [6] Source: Personal archive …”
Section: Complicationsmentioning
confidence: 99%